Implants in the elderly patient - Schlegel, Karl Andreas; Schmitt, Christian; Möst, Tobias (Implantologie, 2020)
In our daily practice more and more patients show up who have received dental implants thirty or fourty years ahead. These patients are today related as "golden agers". At the same time in our days we can see that age related contraindications for implants are very liberal and no definite age limitation is valide any more. With some cases treated in the own office the reliability and problems of such aged patients should be highlighted. Also the question "quality of life" versus potential risks of these therapy options should be counterbalanced and at least when planning new implant borne rehablitations should be brought into consideration.
CRIS-Team WoS Importer:2021-02-05